Theories of financial disturbance : an examination of critical theories of finance from Adam Smith to the present day - Toporowski, Jan (Cheltenham, UK ; Northhampton, MA : Edward Elgar, 2005)
Theories of Financial Disturbance examines how the operations of market-driven finance may initiate and transmit disturbances to the economy at large, by looking in detail at how various economists envisaged such disturbances occurring.
Includes bibliographical references (p. 172-188) and index.
aia 15/8/16
Loans
Keywords: Finance; Finance- History; Macroeconomics; Finance; Business cycles